Dulce María Loynaz, Fina García Marruz y la poesía de lo pequeno - Cecere, Fabiola (Verba hispanica, 2015)
Dulce María Loynaz and Fina García Marruz are two poets who stand out in the rich heritage of Cuban literature for the linguistic vitality of their verses, their vivid images, their evocative use of language and for embodying, in their own way, the life history, customs, contradictions and all the glorious colour of the island. We shall explore some of the poetic questions and themes debated by the authors in the poems. They reveal an antithetical conception of poetry but, at same time, a common root. The comparative analysis will reflect on the linguistic rigour choosen by Dulce María Loynaz in her lyric intimacy, on the hand and on Fina García Marruz%s pursuit of the eternal in the fleeting temporal things.
Keywords: Loynaz, Dulce María, 1902-1997; García Marruz, Fina, 1923-; kubanska poezija; 20.st.; pesnice